In-wheel permanent magnet motor. - Misron, Norhisam; Abdullah, Ami Nurul Nazifah; Raja Othman, Raja Nor Firdaus Kashfi (2009)
The present invention is about an in-wheel permanent magnet motor for agriculture application. This developed motor is intended for high toque and low speed applications. It consists of two main parts which are stator and rotor. The stator consist of coils where as rotor consist of permanent magnet. The novelty of this invention can be seen through specially design group phases of coil in stator and the permanent magnet is embedded and arranged back to back. As result it produced high torque and can be operated as stepper motor, synchronous motor or brushless DC motor.